PENGARUH ANGGARAN BERBASIS KINERJA TERHADAP EFEKTIVITAS PENGENDALIAN ANGGARAN DI DINAS PENDAPATAN DAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN BANDUNG BARAT - M Sandi Marta; Dedeh Kurniasari; Dewi Kurniasari (Universitas Merdeka Malang, 2017)
Research in budget control field has magnetized the interest of many researchers as a tool of development for many countries. This study examined the impact of Performance Based Budgeting on effectiveness of control budget. To achieve the above objective a survey of over 33 employee of DPKAD. Data was analyzed through descriptive and inferential statistical analysis. The results demonstrate that Performance Based Budgeting has positive impact on effectiveness of control budget.DOI: https://doi.org/10.26905/pjiap.v2i2.1446